NR1H4 rs35724 G>C variant modulates liver damage in nonalcoholic fatty liver disease. (29th July 2021) - Grimaudo, Stefania; Dongiovanni, Paola; Pihlajamäki, Jussi; Eslam, Mohammed; Yki‐Järvinen, Hannele; Pipitone, Rosaria Maria; Baselli, Guido; Cammà, Calogero; Di Marco, Vito; Enea, Marco; Longo, Miriam; Pennisi, Grazia; et al.
Abstract: Background and Aims: Farnesoid X receptor (FXR) plays a key role in bile acid and lipid homeostasis. Experimental evidence suggests that it can modulate liver damage related to nonalcoholic fatty liver disease (NAFLD). We examined the impact of the NR1H4 rs35724 G>C, encoding for FXR, on liver damage in a large cohort of patients at risk of steatohepatitis. Methods: We considered 2, 660 consecutive individuals at risk of steatohepatitis with liver histology. The rs35724 G>C polymorphisms were genotyped by TaqMan assays. Gene expression was evaluated by RNASeq in a subset of patients (n = 124). Results: The NR1H4 rs35724 CC genotype, after adjusting for clinic‐metabolic and genetic confounders and for enrolling centre, was protective against severity of steatosis (GG vs CC OR 0.77, 95% CI 0.62‐0.95; P  = .01), steatohepatitis (GG vs CC OR 0.62, 95% CI 0.47‐0.83; P  = .001) and severity of fibrosis (GG vs CC OR 0.83, 95% CI 0.67‐0.98; P  = .04). The C allele was associated with higher total circulating cholesterol ( P  = .01). Patients carrying the NR1H4 rs35724 C allele had significantly higher hepatic mRNA levels of FXR and were associated with higher hepatic FGFR4 and Cyp39A1 that are in turn involved in bile acid synthesis. Conclusions: Increased hepatic FXR expression due to the NR1H4 rs35724 C allele is linked to higher serum cholesterol but protects against steatosis, steatohepatitis and liver fibrosis. The translational relevance of these results for patient risk stratification and FXR‐targeted therapy warrants further investigation.